Structures composing protein domains - Kubrycht, Jaroslav; Sigler, Karel; Souček, Pavel; Hudeček, Jiří (Biochimie, 2013)
This review summarizes available data concerning intradomain structures (IS) such as functionally important amino acid residues, short linear motifs, conserved or disordered regions, peptide repeats, broadly occurring secondary structures or folds, etc. IS form structural features (units or elements) necessary for interactions with proteins or non-peptidic ligands, enzyme reactions and some structural properties of proteins. These features have often been related to a single structural level (e.g. primary structure) mostly requiring certain structural context of other levels (e.g. secondary structures or supersecondary folds) as follows also from some examples reported or demonstrated here. In addition, we deal with some functionally important dynamic properties of IS (e.g. flexibility and different forms of accessibility), and more special dynamic changes of IS during enzyme reactions and allosteric regulation. Selected notes concern also some experimental methods, still more necessary tools of bioinformatic processing and clinically interesting relationships.
Keywords: Humans; terciární struktura proteinů; lidé; proteiny; Protein Structure, Secondary; katalytická doména; Protein Structure, Tertiary; Sequence Alignment; Catalytic Domain; sekvenční seřazení; Proteins; sekundární struktura proteinů